Sex ratio at birth in Kogi state, North-Central Nigeria - Adekunle Bakare; Deborah Peter; Motunrayo Mojoyin Coker; Silas Fagbenro; Okunola A. Alabi (Kashmir Journal of Science)
The human secondary sex ratio is the male-to-female ratio at birth. Studies have shown that due to some factors, there has been deviation towards one sex in different populations. There has been no report on the sex ratio at birth (SRB) from Kogi State, North-Central Nigeria. We conducted a retrospective study on the SRB in the three geopolitical zones of Kogi State covering six federal and state hospitals, and factors that might have influenced the process. Data on childbirth from 1991 to 2020 collected from the Federal Medical Centre Lokoja, General Hospital Mopa-Muro, Zonal Hospital Kabba, Specialist Hospital Obangede, Zonal Hospital Okene, and Prince Audu Abubakar University Teaching Hospital Anyigba were analyzed using descriptive statistics. The annual SRB was 98.1:100, 104.6:100, 101.5:100, 108.3:100, 102.2:100, and 104.9:100 for the six hospitals, respectively. The pooled data had an SRB of 100.7:100 for Kogi State indicating slightly more male than female births. There was no significant difference (p>0.05) between the variations in sex ratio. The SRB might have been influenced by the preference for male children, the use of oral contraceptives, family size, urbanization, and socioeconomic factors.